Sustainability on institutional logics perspective : the experience of Brazilian School Feeding Program - Bonotto, Mariana Manfroi da Silva (2022)
The institutional orders are the core elements to understand the role of culture on society’s behavior, according to the Institutional Logics Perspective (ILP). The central logic of family, community, state, democracy, professions, corporations, market, and religion offer a symbolic system and material practices capable of guiding the system of beliefs, values, norms, and symbols of social collectives (Thornton, Ocasio and Lounsbury, 2015). But the social actor’s transit between these logics that are interdependent and potentially contradictory (Friedland and Alford, 1991) brings a complex process of shaping your world view. Over time, sustainability has come to represent one more element capable of shaping individual and organization’s reality´s construction. Especially because of the negative effects of the accumulation regime that spread all over the globe, traduced as social and environmental problems and inequality of the economic system that affects all humanity, regardless of which side you are on. This study presents a sequence of papers that invite the reader to immerse themselves in the institutional order of sustainability. The general objective is to analyze the institutional logics, institutional change process, institutional complexity, and organizational responses arising from the sustainability, considered as an institutional order, expressed in the normative foundation and implementation environment of the Brazilian School Feeding Program (PNAE). From a discussion on institutional logics at the macro-social level, the paper I describe the formation, stabilization, and legitimation that mark the constitution of sustainability as an institutional order. It is argued, based on the critical literature on sustainable development, about the capacity to form different institutional logics in this order, mapping the elements of three ideal types: the logic of environmental protection, social justice, and economic growth. For the order of sustainability, besides traditional institutional change mechanisms, social movements play the role of triggers in an institutional change in the formation of sustainability logics. The study advances theoretically by recognizing sustainability as an institutional order, bringing a theoretical-methodological proposal that helps to map the logic of sustainability and contributes to the formation of strategies to develop sustainability at different levels of analysis, making it possible to apply it in other contexts. Based on the theoretical proposal of the order of sustainability, the paper II, aims to analyze at the field level the reflection of a public policy that walked integrated into the history of the Brazilian agri-food system, influencing and being influenced by transactions that affect the production, commercialization, and consumption of food from a logic focused on sustainability. The study revealed that the program presented, until assuming the sustainability logic, two distinct institutional logics, the assistance logic, which has dominated the program since its inception, from 1955 to 1994, when the phase of "precipitating jolts" occurs. From there to the stabilization of the sustainability logic, the program was conducted in hybrid logic, which can be considered a transitional phase in which “deinstitutionalization” and “preinstitutionalization” occurred. On sustainability logic, the final phases of the change process occurred, “theorizing”, “diffusion”, and “reinstitutionalization”, ending the institutional change process. The claims of the social movement were one of the triggers for the institutional change process to the sustainability logic. The social movements contributed substantially to the insertion of the family farming products on the public purchases for school meals, one of the main reasons to characterize the program as a sustainable model of the school feeding program. It can be inferred that the sustainable model of the PNAE contributed to the historical formation of the civic order (Niederle and Junior, 2018) of the Brazilian agrifood system, which carries its elements of the order of sustainability, anchored in precepts of food sovereignty, food and nutrition security and the human right to adequate food. The paper shows an institutional change process guided by the institutional order of sustainability, contributing to the development of the ILP, and provides an in-depth analysis of the trajectory of the PNAE in the light of the transformations of the agri-food system. After analyzing the normative trajectory of the program, which gave it the responsibility of guiding the implementation of sustainable school feeding programs in several countries around the world, paper III sought to understand the environment of institutional complexity that affect the relationships aimed at the need to implement the PNAE at the local level and understand the type of organizational response generated from this complexity. The claims of the social movement were one of the triggers for the institutional change process to the sustainability logic. The social movements contributed substantially to the insertion of the family farming products on the public purchases for school meals, one of the main reasons to characterize the program as a sustainable model of the school feeding program. It can be inferred that the sustainable model of the PNAE contributed to the historical formation of the civic order (Niederle and Junior, 2018) of the Brazilian agrifood system, which carries its elements of the order of sustainability, anchored in precepts of food sovereignty, food and nutrition security and the human right to adequate food. The paper shows an institutional change process guided by the institutional order of sustainability, contributing to the development of the ILP, and provides an in-depth analysis of the trajectory of the PNAE in the light of the transformations of the agri-food system. After analyzing the normative trajectory of the program, which gave it the responsibility of guiding the implementation of sustainable school feeding programs in several countries around the world, paper III sought to understand the environment of institutional complexity that affect the relationships aimed at the need to implement the PNAE at the local level and understand the type of organizational response generated from this complexity. The findings suggest that the sustainability, professional, market, state, community, and democracy develop a state of complexity in PNAE´s implementation that has adherence and legitimacy. The state logic is present on the program’s mission, which is to provide healthy food, through PNAE Standards, to all students enrolled in the basic public education from the municipality´s school. The sustainability and professional logic tempered the action of market logic, especially when it comes to purchases of food from family farming. The community and democracy logics are present in the governance mechanism. As an organizational response, in all cases, the strategy adopted by the local public administration is a “compromise”, that is, balancing the expectations by providing the structure partially to full implementation of PNAE guidelines. This paper highlights the necessity for public administration reassess your program management strategy to provide adequate support for compliance with all PNAE´s legal requirements that translate into actions aimed at sustainability practices. The contribution of this multiple case study to the ILP is the understanding of the effects generated by the social direction of sustainability as an institutional order. Two empirical aspects could be seen, first in terms of the behavior of sustainability logics integrating a state of complexity and the second, the organizational responses in this environment. The trilogy of papers contributes to the theoretical and empirical advance of ILP and the PNAE, presenting important insights between social public policies and sustainability in the search for sustainable development.